Affective response during physical activity: Within-subject differences across phases of behavior change - Dunton, Genevieve F; Leventhal, Adam M; Rothman, Alexander J; Intille, Stephen S (Health psychology, 2018)
Affective response during physical activity may be a key factor reinforcing future behavior. However, little is known about how affective responses during physical activity may differ across phases of behavior change. This study used real-time Ecological Momentary Assessment (EMA) to examine within-subject differences in affective response during physical activity in daily life as individuals transitioned across phases of behavior change. A sample of 115 adults (M = 41.0 years, 74% female) participated in an intensive longitudinal study with measurement bursts at 0, 6, and 12-months. Each burst consisted of 8 randomly-prompted EMA occasions per day across 4 days. EMA self-report items assessed current activity level (i.e., physical activity or nonphysical activity), and positive and negative affect. Questionnaires measured phase of behavior change (e.g., preaction [no regular physical activity], action [regular physical activity <6 months], and maintenance [regular physical activity ≥6 months]) at each burst. Three-level (Level-1 = occasion, Level-2 = burst, Level-3 = person) linear regression models tested Phase of Change (Level-2, within-subject) × Physical Activity Level (Level-1, within-subject) interactions controlling for day of week, time of day, and sex. Positive affective response during physical activity (vs. nonphysical activity) was higher when individuals were in preaction phases (vs. action). Negative affective response during physical activity (vs. nonphysical activity) was lower when individuals were in the maintenance phase (vs. action). Long-term maintenance of physical activity may be particularly challenging, given the lack of positive reinforcement that is thought to be needed to sustain behavior. (PsycINFO Database Record